COMPARATIVE ANALYSIS EXPERT SYSTEM OF CERTAINTY FACTOR METHOD WITH DEMPSTER SHAFER METHOD BY USING OPEN DECISION MAKER TOOL FOR TODDLER AT VACCINE HOUSE - Rahayu, Eka Fitri (Universitas Gunadarma, 2020)
Expert system is a form progress of Information and Communications Technology. Development of an expert system can be performed in variety areas, including health. In its development required a result can be trusted by the user. Therefore it required the value of belief for any decision issued by the expert system.In expert system, there are several uncertainty methods can be used namely Certainty Factor, Dempster Shafer, Naïve Bayes, Fuzzy Logic, etc. Therefore, in this study will be performed the comparison between Certainty Factor and Dempster Shafer method using data infectious diseases in toddler. Both of methods have different ways of working in the calculation, but both are equally give results to support a decision.In the comparative analysis of both methods will be used a decision support system tool namely Open Decision Maker with Analytical Hierarchy Process approach. From the comparison result of eight cases has been obtained that the Certainty Factor method have more higher belief values as big as 82.54% than Dempster Shafer method as big as 17.46%, but significantly the value of belief between the two was not differ greatly.